2022
DOI: 10.3390/nu15010004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intake of Both Caffeine and Non-Caffeine Coffee Components Is Associated with Reduced NAFLD Severity in Subjects with Type 2 Diabetes

Abstract: Coffee may protect against non-alcoholic fatty liver disease (NAFLD), but the roles of the caffeine and non-caffeine components are unclear. Coffee intake by 156 overweight subjects (87% with Type-2-Diabetes, T2D) was assessed via a questionnaire, with 98 subjects (all T2D) also providing a 24 h urine sample for quantification of coffee metabolites by LC–MS/MS. NAFLD was characterized by the fatty liver index (FLI) and by FibroscanÒ assessment of fibrosis. No associations were found between self-reported coffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Obese smokers were more likely to suffer from NAFLD. Caffeine, the main ingredient of coffee, was reported to have a protective effect on NAFLD, with good application prospects (29,30) . Moreover, caffeine was proven to relieve NAFLD induced by HFD (20) , but it is still unknown whether caffeine can alleviate the development of NAFLD caused by HFD plus nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Obese smokers were more likely to suffer from NAFLD. Caffeine, the main ingredient of coffee, was reported to have a protective effect on NAFLD, with good application prospects (29,30) . Moreover, caffeine was proven to relieve NAFLD induced by HFD (20) , but it is still unknown whether caffeine can alleviate the development of NAFLD caused by HFD plus nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the BMI and specific weights of the mice are unclear, body weight may also be an essential factor mediating coffee-associated effects on the liver. Later findings by Coelho et al [ 36 ] also show that the effect of coffee on the liver may be related to an individual’s body mass.…”
Section: Reviewmentioning
confidence: 95%
“…Studying T2D as well, Coelho et al [ 36 ] conducted a survey-based cross-sectional study to investigate the role of coffee components in the MASLD progression of 98 subjects with T2D (Table 1 ). All subjects completed a questionnaire on their consumption of caffeinated beverages and foods and provided a 24-hour urine sample for investigation of coffee metabolites.…”
Section: Reviewmentioning
confidence: 99%
“…It has also been suggested that caffeine attenuates liver fat and stiffness in patients with diabetes and NAFLD ( 83 ). Coffee is associated with NAFLD severity in type 2 diabetics ( 84 ). For overweight/obese patients with MASLD and T2D, coffee consumption may have potential benefits ( 85 ).…”
Section: Lifestyle Interventions Of Mafldmentioning
confidence: 99%